Analisis Nilai Ekonomi Pemanfaatan Air Di Daerah Aliran Sungai (DAS) Cijengkol - Maylani, Gina; Sutikno, Sugeng (MESA (Teknik Mesin, Teknik Elektro, Teknik Sipil, Teknik Arsitektur), 2024)
Surface water is the portion of precipitation that flows over the land surface into rivers, lakes, or oceans. One source of surface water in West Java is river water originating from the Cijengkol watershed. Communities living around the Cijengkol River have traditionally benefited from the value of water as a river environmental service. They use water for their livelihood, mainly for agriculture, fishing, and animal husbandry. In addition, the water in the Cijengkol watershed is also used for daily needs by the people living around the Cijengkol river. This study explains the value of water utilization used by the community around the Cijengkol watershed from various sectors, namely agriculture, household needs, animal husbandry and fisheries and examines the value of the economic benefits of water use in the Cijengkol watershed. The research method used is to find the mainstay discharge and approach the formula for the Economic Value of Water with data obtained from Perum Jasa Tirta II (PJT II), Regional Drinking Water Company (PDAM), and the Regency Central Statistics Agency (BPS). Subang. It can be seen that the mainstay debit for irrigation is 5.61 mÂ³/s while for household needs it is 4.24 mÂ³/s. The economic value of water in the Cijengkol watershed is Rp. 949,986,603,420/year. from various aspects of use, namely household needs, agriculture, fisheries, and animal husbandry.